Distinctive striatal dopamine signaling after dieting and gastric bypass. (May 2015) - Hankir, Mohammed K.; Ashrafian, Hutan; Hesse, Swen; Horstmann, Annette; Fenske, Wiebke K.
Highlights Palatable foods elicit striatal dopamine release to strongly influence feeding. Obesity is associated with aberrant striatal dopamine signaling. Imbalance in striatal dopamine signaling may promote post-dieting weight regain. Surgery may correct striatal dopamine signaling to modify fat reward value.